Overexpression of a citrus basic helix-loop-helix transcription factor (CubHLH1), which is homologous to Arabidopsis activation-tagged bri1 suppressor 1 interacting factor genes, modulates carotenoid metabolism in transgenic tomato. (February 2016) - Endo, Tomoko; Fujii, Hiroshi; Sugiyama, Aiko; Nakano, Michiharu; Nakajima, Naoko; Ikoma, Yoshinori; Omura, Mitsuo; Shimada, Takehiko
Highlights: CubHLH1 has a similar function of ATBS1 interacting factor (AIF) of BR signalling component. Overexpression of CubHLH1 caused dwarf phenotype and lycopene reduction in transgenic tomato. The transcript of CubHLH1 abundantly was accumulated in citrus mature fruit. CubHLH1 might be involved in carotenoid metabolism in citrus mature fruit. Abstract: To explore the transcription factors associated with carotenoid metabolism in citrus fruit, one transcription factor ( CubHLH1 ) was selected through microarray screening in Satsuma mandarin ( Citrus unshiu Marc.) fruit, which was treated with exogenous ethylene or gibberellin (GA), accelerating or retarding carotenoid accumulation in peel, respectively. The amino acid sequence of CubHLH1 has homology to Arabidopsis activation-tagged bri1 suppressor 1 ( ATBS1 ) interacting factor (AIF), which is functionally characterized as a negative regulator of the brassinolide (BR) signalling pathway. Yeast two-hybrid analysis revealed that protein for CubHLH1 could interact with Arabidopsis and tomato ATBS1. Overexpression of CubHLH1 caused a dwarf phenotype in transgenic tomato ( Solanum lycopersicum L.), suggesting that CubHLH1 has a similar function to Arabidopsis AIF. In the transgenic tomato fruit at ripening stage, the lycopene content was reduced along with the changes in carotenoid biosynthetic gene expression. The abscisic acid (ABA) content of all the transgenic tomato fruit was higher than that of the wild type. These results implied that CubHLH1 is considered to have a similar function to Arabidopsis AIFs and might be directly involved in carotenoid metabolism in mature citrus fruit.